Nigella Sativa-Based Protection against Uterus and Ovary-Related Histological Damages Generated by Cimetidine in Mice - Wafaa Sameer Abdullah (Journal of Global Pharma Technology, 2018)
To generate protecting effects against the histopathological changes in uteri and ovaries in mice that are caused by cimetidine, this work was initiated using the aqueous suspension of Nigella sativa. In this experiment, 40 female mice were recruited that were randomly divided into 4 groups. Nigella sativa-cimetidine group (NCG) was given orally 1000mg/kg B.W of Nigella sativa-based aqueous suspension (NSAS) daily that was followed by administering cimetidine at 25mg/kg B.W. Nigella sativa group (NG) was administered orally 1000mg/kg B.W of NSAS daily. Cimetidine group (CTG) was exposed to 25mg/kg B.W of cimetidine daily. Control group (CG) received normal saline only. The experiment was run for 76 days. After the experiment was done, animals were sacrificed to obtain uteri and ovaries from all groups. These organs were subjected to histopathological-based processing and microscopically examination. The results of applying cimetidine alone in the CTG revealed harmful changes that interfered with the normal physiological activities in these organs that were ceased after using NSAS in the NCG. The study provides valued and important information about the use of Nigella sativa and its extracts in generating protection against the genital-based harmful changes induced by cimetidine.Keywords: Cimetidine, Nigella sativa, protection.